An update on the US adult thalassaemia population: a report from the CDC thalassaemia treatment centres. (14th November 2021) - Chapin, John; Cohen, Alan R.; Neufeld, Ellis J.; Vichinsky, Elliott; Giardina, Patricia J.; Boudreaux, Jeanne; Le, Binh C.; Kenney, Kristy; Trimble, Sean; Thompson, Alexis A.
Summary: Thalassaemia is caused by genetic globin defects leading to anaemia, transfusion‐dependence and comorbidities. Reduced survival and systemic organ disease affect transfusion‐dependent thalassaemia major and thalassaemia intermedia. Recent improvements in clinical management have reduced thalassaemia mortality. The therapeutic landscape of thalassaemia may soon include gene therapies as functional cures. An analysis of the adult US thalassaemia population has not been performed since the Thalassemia Clinical Research Network cohort study from 2000 to 2006. The Centers for Disease Control and Prevention supported US thalassaemia treatment centres (TTCs) to compile longitudinal information on individuals with thalassaemia. This dataset provided an opportunity to evaluate iron balance, chelation, comorbidities and demographics of adults with thalassaemia receiving care at TTCs. Two adult cohorts were compared: those over 40 years old ( n = 75) and younger adults ages 18–39 ( n = 201). The older adult cohort was characterized by higher numbers of iron‐related comorbidities and transfusion‐related complications. By contrast, younger adults had excess hepatic and cardiac iron and were receiving combination chelation therapy. The ethnic composition of the younger cohort was predominantly of Asian origin, reflecting the demographics of immigration. These findings demonstrate that comprehensive care and periodic surveys are needed to ensure optimal health and access to emerging therapies.